Workbook/Anthology for Music Theory : Problems and Practices in the Middle Ages and Renaissance. - Ultan, Lloyd, 1929-1998 (University of Minnesota Press, 1977)
This workbook contains 68 musical examples from the middle ages and the Renaissance. Specific assignments for students are designed to correlate with the material presented in Music Theory: Problems and Practices in the Middle Ages and Renaissance by Lloyd Ultan.